Dengue Knowledge and Preventive Practices among Rural Residents in Samar Province, Philippines - Leodoro Jabien Labrague; Begonia C Yboa (International Journal of Public Health Science (IJPHS), 2013)
The World Health Organization (WHO) classifies dengue as a diseaseimportant in public health. The epidemiology and ecology of dengueinfections are strongly associated with human habits and activities. Thepresent study aimed to evaluate the knowledge and practices regardingdengue infections among rural residents in Samar Province, Philippines. Across sectional design was adopted for this investigation A conveniencesamples of six hundred forty six (646) residents who were visiting the ruralhealth units in different municipalities of Samar, Philippines were taken asparticipants in study. More than half of the respondents had good knowledge(61.45%) on causes, signs and symptoms, mode of transmission, andpreventive measures about dengue. More than half of the respondents useddengue preventive measures such as fans (n = 340, 52.63%) , mosquito coil(n = 458, 70.90%), and bed nets (n = 387, 59.91%) to reduce mosquitoeswhile only about one third utilized insecticides sprays (n = 204, 31.58%) andscreen windows (n = 233, 36.07%) and a little portion used professional pestcontrol (n = 146, 22.60%). There was no correlation between knowledgeabout dengue and preventive practices (p=0.75). Television/Radio was citedas the main source of information on dengue infections. Findings suggest thatbetter knowledge does not necessarily lead to better practice of denguemeasures. Educational campaigns should give more emphasis on costeffective ways of reducing mosquito and preventing dengue such asenvironmental measures and control. Furthermore, wide range ofinformation, skills and support must be provided by the government toincrease dengue awareness among residents. DOI: http://dx.doi.org/10.11591/ijphs.v2i2.2511